Tinjauan Sadd al Dzari’ah Terhadap Larangan Pegawai Negeri Sipil Wanita Menjadi Istri Kedua, Ketiga, dan Keempat - Kartika, Elza Putri; Khairuddin, Khairuddin; Rohmadi, Rohmadi (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract : (1) How is the review of Indonesia’s positive law towards female Civil Servants becoming the first wife in polygamous marriages, and (2) How is the review Sadd Al-Dzari’ah against female civil servants who become wives in polygamous marriages. The purpose of this study is to explain how the analysis of the concept of Prohibition of Civil Servants for women to become wives in polygamous marriages is reviewed Sadd Al-Dzari’ah. The type of research in this thesis is library researchin obtaining data, information, and facts that the author uses various kinds of books related to the subject matter. From the results of this research it was found that (1) Positive laws against female Civil Servants as stated in Government Regulation no. 45 of 1990 Article 4 Paragraph 2 relating to Law Number 1 of 1974 aims at the principle of monogamy and efforts to reduce problems that could disrupt the work of a civil servant and protect the behavior of civil servants who are exemplary, and (2) Sadd Al-Dzari's review 'ah regarding the prohibition on female Civil Servants (PNS) becoming wives in polygamous marriages, where the intention of polygamy is not in accordance with Islamic law so that the prohibition on female Civil Servants becoming second, third or fourth wives is in Government Regulation Number 45 of 1990 Article 4 Paragraph This No. 2 functions to protect the rights of the wife and first child and protect family harmony, so that the performance of Civil Servants in the government system mechanisms runs well and maintains the good name of the government.Keywords: Sadd Al-Dzari’ah, Female Civil Servants, and Polygamy Abstrak: (1) Bagaimana tinjauan hukum positif Indonesia terhadap Pegawai Negeri Sipil (PNS) wanita menjadi istri dalam perkawinan poligami, dan (2) Bagaimana tinjauan Sadd Al-Dzari’ah terhadap Pegawai Negeri Sipil (PNS) wanita yang menjadi istri dalam perkawinan poligami. Tujuan penelitian ini adalah untuk menjelaskan bagaimana analisa konsep Larangan Pegawai Negeri Sipil (PNS) wanita menjadi Istri dalam perkawinan poligami yang ditinjau Sadd Al-Dzari’ah, Adapun jenis penelitian kepustakaan dalam mendapatkan data, informasi, dan fakta yang ada penulis menggunakan berbagai macam buku yang berkaitan dengan pokok permasalahan. Dari hasil penelitian ini ditemukan bahwa (1) Hukum positif terhadap Pegawai Negeri Sipil wanita yang tertuang dalam Peraturan Pemerintah No. 45 Tahun 1990 Pasal 4 Ayat 2 berkaitan dengan Undang-Undang Nomor 1 Tahun 1974 ini tujuannya ke arah asas monogami dan upaya mengurangi masalah yang bisa membuat terganggunya perkerjaan seorang PNS dan melindungi perilaku PNS yang menjadi teladan, dan (2) tinjauan Sadd Al-Dzari’ah terhadap larangan Pegawai Negeri Sipil (PNS) wanita yang menjadi istri dalam perkawinan poligami, dimana niat poligami tidak sesuai dengan syariat Islam sehingga larangan wanita Pegawai Negeri Sipil menjadi istri kedua, ketiga, atau keempat dalam Peraturan Pemerintah Nomor 45 Tahun 1990 Pasal 4 Ayat 2 ini, berfungsi melindungi hak-hak istri dan anak pertama serta melindungi keharmonisan keluarga, sehingga kinerja Pegawai Negeri Sipil dalam mekanisme sistem pemerintahan berjalan dengan baik dan menjaga nama baik pemerintahan.Kata Kunci : Sadd Al-Dzari’ah , Pegawai Negeri sipil Wanita, dan Poligami